2013
DOI: 10.3892/ijo.2013.2067
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lysyl oxidase in human osteosarcoma and its clinical significance: A tumor suppressive role of LOX in human osteosarcoma cells

Abstract: Lysyl oxidase (LOX) is an extracellular matrix (ECM) remodeling enzyme, which is involved in the development and progression of many types of tumors. LOX dysfunction is observed in colorectal, breast and ovarian cancer. However, the precise effects and molecular mechanisms of LOX action in osteosarcoma progression are still unknown. We evaluated the role of LOX in human osteosarcoma cell lines and clinical tumor samples in order to determine the function of this molecule. In our study, we showed that the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…It promotes cell growth and metastasis of a variety of cancer cells in vitro and in vivo [10,11,28,31,32], whereas other researchers found that LOX is a suppressor of proliferation and migration in human osteosarcoma cells [6]. In our study, the data from MTT assay demonstrated that siLOX intensively inhibited proliferative activity of MHCC-97-H and HepG2 cells.…”
Section: Knockdown Of Lox Affects Tgf-b-induced Upregulation Of Vegf mentioning
confidence: 46%
See 2 more Smart Citations
“…It promotes cell growth and metastasis of a variety of cancer cells in vitro and in vivo [10,11,28,31,32], whereas other researchers found that LOX is a suppressor of proliferation and migration in human osteosarcoma cells [6]. In our study, the data from MTT assay demonstrated that siLOX intensively inhibited proliferative activity of MHCC-97-H and HepG2 cells.…”
Section: Knockdown Of Lox Affects Tgf-b-induced Upregulation Of Vegf mentioning
confidence: 46%
“…and breast cancer [9][10][11], although evidence also points to LOX as a tumor suppressor [6], which indicates a dual role of LOX. Recent studies have shown that elevated expression of LOX propeptide, a LOX suppressor, inhibits the growth and migration of HCC cells [12], suggesting the involvement of LOX in HCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Other findings indicated that the effects of LOX may be mediated via the PI3K/AKT signaling pathway. 32 Kucharzewska et al reported that hypoxia/ LOX signaling activates PI3K/Akt pathway. 33 As PI3k/Akt pathway per se is oncogenic, activation of PI3k/Akt leads to DSB and genomic instability, 33,34 and it may also participate in angiogenesis, cell cycle arrest, and resistance to radiationinduced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos estudos de LOX foi realizada em tumores de mama, cabeça e pescoço, pulmão, colorretal, pâncreas, osteosarcoma e estômago Gao et al, 2010;Min et al, 2010;Lee et al, 2011;Sanchez et al, 2011;Bais et al, 2012;Eiseler et al, 2012;Xu et al, 2013;, Kim et al, 2014.…”
Section: Expressão Gênica Da Família Das Lisil Oxidases Bmp1 E Hif1a unclassified